Prevalence of Haemoglobine s in Araraquara-SP Population. (Revista Brasileira Multidisciplinar, 2008)
The Sickle Cell Anemia is a genetic hemoglobionopathy, characterized by an alteration in the hemoglobin molecule struture (HbA1), called hemoglobin S (HbS), which causes a distortion in the erythocytes structure, changing from spherical shape to sickle shape (sickle-cell), a sickling phenomenon, which leads to severe anemia in homozygous, while sickle cell trait (heterozygote) leads to pain crisis, according to pathophysiology, in low O2 blood pressure situations. The most specific and sensitive test used to diagnose this anemia is the hemoglobin eletrophoresis test, which is, however, hard to be incorporated in routine laboratories, due to its high cost. The objective of this work was to estimate the sickle cell trait prevalence in Araraquara - SP population. The prevalence of asymptomatic individuals with the sickle cell trait was 1.5%. Considering the study of race prevalence, 0,6% of sickle cell trait in white individuals and 15,4% in black ones were found.
Keywords: Anemia; Hemoglobin; Sickle Cell; Sickling; Solubility.